Penerapan QR Code Menggunakan Webcam Pada Sistem Absensi Guru Honorer Dengan Metode Rapid Application Development (RAD) di SDN Karang Asih 06 - Andri Firmansyah; Sovia Yunanda (DPPM Universitas Pelita Bangsa, 2024)
Attendance is a very important process, one of which is in the world of education, of course not only for students, teachers are also required to carry out the attendance process in order to determine the quality of their work as teachers at school. The Attendance System for Honorary Teachers is still very simple at SDN Karang Asih 06. Where the system still uses paper containing signatures. of course this system is still very manual for an educational institution because of the lack of discipline so that there are often obstacles such as data recapitulation, or can be misused by irresponsible parties. System research uses the Rapid Application Development (RAD) method which has 3 main stages, namely: (1) Requirment Planning, (2) Design Process (Design Workshop), (3) Implementation. And the choice of a desktop-based attendance system using this QR Code is because it is more efficient and practical in inputting attendance and conveying information from the results of attendance data. Of course, this system is a new standard in the school environment of SDN Karang Asih 06, which previously took attendance manually using paper. In the early stages of system implementation, users must input their attendance using the C# programming language (Sharp), and the system stores attendance data in the MySQL database which can be used as attendance information. And it is hoped that this attendance system can be better and can improve the shortcomings in the attendance system that has been implemented previously.